Kampung Bhinneka: Developing a Multicultural Tourism Village Based on Community Religious Diversity - Prasetyo, Kuncoro Bayu; Pramono, Didi; Putri, Noviani Achmad (Universitas Islam Negeri Madura, 2025)
Religious aspects are prominent determinants that shape diversity in Indonesia and have implications for problems of inter-religious relations related to intolerance and radicalism. This condition is a significant threat to national disintegration. The purpose of this study is to identify the potential of the social, cultural, and natural capital of local communities related to socio-religious diversity and to utilize this potential in the form of a multi-religious tourist village as a role model for learning and disseminating multicultural values ​​through multicultural educational tourism activities. The research was conducted in Kalisat Hamlet, Temanggung, Central Java, using research and development methods and participatory rural appraisal for participatory community development. The research stages began with identifying potential and problems in designing and developing a multi-religious-based tourist village model. The study results show that Kalisat Hamlet has excellent social, cultural, and natural potential as capital for developing the Kampung Bhinneka tourist village. The most prominent main point is the diversity of religions embraced by the Kalisat community, namely Buddhism, Islam, Christianity, and Sapta Dharma. In this diversity, the people of Dusun Kalisat live in harmony. With the support of infrastructure, management, local government support, and promotional media, Kampung Bhinneka in Dusun Kalisat will be able to become an alternative tourist destination that offers the concept of learning to live in a diverse society.